THE ROLE OF LITHOSPHERIC MANTLE HETEROGENEITY IN THE GENERATION OF PLIO-PLEISTOCENE ALKALI BASALTIC SUITES FROM NW HARRAT ASH SHAAM (ISRAEL) - Weinstein Y.; Navon O.; Stein M.; Altherr R. (My University, 2006)
Plio-Pleistocene volcanism in the Golan and Galilee (northeastern Israel) shows systematic variability with time and location: alkali basalts were erupted in the south during the Early Pliocene, whereas enriched basanitic lavas erupted in the north during the Late Pliocene (Galilee) and Pleistocene (Golan). The basalts show positive correlations in plots of ratios of highly to moderately incompatible elements versus the concentration of the highly incompatible element (e.g. Nb/Zr vs Nb, La/Sm vs La) and in diagrams of REE/HFSE (rare earth elements/high field strength elements) vs REE concentration (e.g. La/Nb vs La). Some of these correlations are not linear but upward convex. 87Sr/86Sr ratios vary between 0.7031 and 0.7034 and correlate negatively with incompatible element concentrations and positively with Rb/Sr ratios. We interpret these observations as an indication that the main control on magma composition is binary mixing of melts derived from two end-member mantle source components. Based on the high Sr/Ba ratios and negative Rb anomalies in primitive mantle normalized trace element diagrams and the moderate slopes of MREE-HREE (middle REE-heavy REE) in chondrite-normalized diagrams, we suggest that the source for the alkali basaltic end-member was a garnet-bearing amphibole peridotite that had experienced partial dehydration. The very high incompatible element concentrations, low K content, very low Rb contents and steep MREE-HREE patterns in the basanites are attributed to derivation from amphibole- and garnet-bearing pyroxenite veins. It is suggested that the veins were produced via partial melting of amphibole peridotites, followed by complete solidification and dehydration that effectively removed Rb and K. The requirement for the presence of amphibole limits both sources to lithospheric depths. The spatial geochemical variability of the basalts indicates that the lithosphere beneath the region is heterogeneous, composed of vein-rich and vein-poor domains. The relatively uniform 143Nd/144Nd (εNd = 4.0-5.2) suggests that the two mantle sources were formed by dehydration and partial melting of an originally isotopically uniform reservoir, probably as a result of a Paleozoic thermal event. © 2006 Oxford University Press.
Keywords: AMPHIBOLE PERIDOTITE; BASANITES; LITHOSPHERIC HETEROGENEITY; MAGMA MIXING; PYROXENITES; Pleistocene; Pliocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен